2009
DOI: 10.1073/pnas.0811353106
|View full text |Cite
|
Sign up to set email alerts
|

Dividing glial cells maintain differentiated properties including complex morphology and functional synapses

Abstract: It is generally believed that dividing cells gain complex features of differentiation only after exiting the cell cycle because cell division and differentiation are both under such tight regulation that their coexistence is deemed unlikely. As the major proliferating cell type in the mammalian CNS, NG2 glial cells (NG2 cells) account for 5-8% of the glial cell population and form synaptic contacts with neurons. Here we report that NG2 cells divide while maintaining their differentiation, including morphologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
118
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(130 citation statements)
references
References 42 publications
11
118
1
Order By: Relevance
“…Synaptic transmission of NG2 cells is an attractive candidate for controlling proliferation and differentiation of these cells in an activity-dependent manner and thus for influencing CNS myelination, although direct evidence is lacking. Indeed, proliferating NG2 cells keep their synapses and transfer them to their progeny during cell division (Kukley et al, 2008;Ge et al, 2009). In addition, there is an increasing axonal glutamatergic "synaptic-like" activity in NG2 cells of the corpus callosum that evolves in parallel with the maturation of the white matter tract (Ziskin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Synaptic transmission of NG2 cells is an attractive candidate for controlling proliferation and differentiation of these cells in an activity-dependent manner and thus for influencing CNS myelination, although direct evidence is lacking. Indeed, proliferating NG2 cells keep their synapses and transfer them to their progeny during cell division (Kukley et al, 2008;Ge et al, 2009). In addition, there is an increasing axonal glutamatergic "synaptic-like" activity in NG2 cells of the corpus callosum that evolves in parallel with the maturation of the white matter tract (Ziskin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We do not know if the cells that were dividing were actively migrating, as has been reported to occur in NG2 glial cells of mice (Ge et al, 2009), or if they were simply paused, or had completed their migration.…”
Section: Development Of the Glial Network In The Antennal Nervementioning
confidence: 92%
“…In the moth, which has a substantive nerve comprising more than 300,000 axons (Sanes and Hildebrand, 1975;Oland and Tolbert, 1989), dividing glial cells also are found throughout the nerve as the population is migrating toward the brain. We do not know if glial cells are proliferating while migrating, as has been shown in NG2 glial cells of mice (Ge et al, 2009) (Silies et al, 2007;Murakami et al, 2007), but elsewhere this part of the process simply is poorly understood, even in systems where good progress has been made in identifying key signaling pathways that initiate and maintain glial migration (Klambt, 2009).…”
Section: Network Formationmentioning
confidence: 99%
“…Moreover, they can occur by synapses becoming integral component, taking part in synaptic signalization [4,6,14]. In hippocampus synantocyte contacts fewer than 20 synapses on average, in comparison with astrocyte which forms about 100.000 of them [15][16][17]. Under electron microscope one observed that axon buttons containing fewer synaptic vesicles form junctions with synantocyte processes in which there is a lack of postsynaptic density [2].…”
Section: Morphological Identification Of Astrocytes and Synantocytesmentioning
confidence: 99%